2012
DOI: 10.1159/000343224
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Monitoring of Midline Shift Predicts Outcome after Intracerebral Hemorrhage

Abstract: <b><i>Background:</i></b> Spontaneous intracerebral hemorrhage (ICH) and the evolution of subsequent perihemorrhagic edema lead to midline shift (MLS), which can be assessed by transcranial duplex sonography (TDS). In this observational study, we monitored MLS with TDS in patients with supratentorial ICH up to day 14 after the ictus, and then correlated MLS with the outcome 6 months after hospital discharge. <b><i>Methods:</i></b> Sixty-eight patients with sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Further, little is known about late ND (LND), even though the existence of LND is well established among clinicians. 4 6 Evidence indicates that structural damage as well as secondary space-occupying lesions in the brain occurs predominantly during the very first days of illness [7][8][9][10][11][12] ( provoking END and LND). Assuming minimisation of complications by means of adequate stroke unit care (including aspiration pneumonia,…”
Section: Introductionmentioning
confidence: 99%
“…Further, little is known about late ND (LND), even though the existence of LND is well established among clinicians. 4 6 Evidence indicates that structural damage as well as secondary space-occupying lesions in the brain occurs predominantly during the very first days of illness [7][8][9][10][11][12] ( provoking END and LND). Assuming minimisation of complications by means of adequate stroke unit care (including aspiration pneumonia,…”
Section: Introductionmentioning
confidence: 99%
“…Formation of perihemorrhagic edema is dynamic [25,26], may last up to 14 days [27] and may peak in the early as well as in the subacute phase [18,28], leading to an increase in ICP that can cause subfalcial and uncal herniation. However, increased ICP may not only appear directly as tissue shift which can be imaged in cross-sectional imaging or TDS, but also indirectly as decreased end-diastolic flow velocity leading to characteristic changes in the Doppler waveform and increased PI [29] (fig.…”
Section: Discussionmentioning
confidence: 99%
“…TDS was performed at the same time points as the TCD examinations with a phased-array ultrasound system equipped with a 1.33-MHz transducer (Siemens Acuson Antares) through the contralateral temporal bone window as described before [12,18]. The third ventricle was visualized in a depth of 6-8 cm and identified by its parallel hyperechogenic margins and the surrounding hypoechogenic thalami.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial duplex sonography (TDS) is a useful noninvasive bedside alternative to CT scan, avoiding increased radiation exposure and repeated transportation of critically ill patients, to monitor MLS in early patient management after ICH. TDS monitoring of the early dynamics of MLS reliably predicts early mortality and outcome in conservatively treated hemispheric ischemic stroke [36]. Studies revealed a high correlation of the imaging of the third ventricle between TDS and CT and a robust inter-and intra-observer reliability.…”
Section: Monitoring Of Midline Shift By Trans-cranial Duplex Sonographymentioning
confidence: 94%